PENERAPAN YURISDIKSI EKSTRATERITORIAL DALAM HUKUM PERSAINGAN USAHA DI INDONESIA TERHADAP TRANSAKSI BISNIS LINTAS BATAS - Widia Novia Shafira (2022)
Business competition policy is an important topic in the scope of global trading. It has consequences that can transcend national boundaries and affect economic policies in a country. As normative judicial law research, the purpose of this study is to analyze the weaknesses of the business competition law in force in Indonesia by making a comparison with the United States which has applied the extraterritorial principle. This legal research uses a state approach, comparative approach, and case approach. The data collected from the book, journal, and Decision Law Number 17/KPPU-1/2010 which states that Pfizer Inc has been involved in conducting cross-border business transactions based on cartel agreement, is processed in this study based on qualitative methods. After conducting the analysis, this legal research concludes that Indonesia does not only need to implement various doctrines applied by the United States such as the single economic entity and effect doctrine, but Indonesia needs to revise Law Number 5 of 1999 concerning Prohibition of Monopoly and Unfair Business Competition. Because it is based on a comparison of the law enforcement between Indonesia and the United States. Thus, with the evasion of Law Number 5 of 1999, legal certainty will be created in the application of extraterritorial principles based on analysis of economic law in the Law of business Competition in Indonesia and can create laws that are capable of dynamic market development.